2013
DOI: 10.1590/abd1806-4841.20131532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of D-dimer serum levels among patients with chronic urticaria, psoriasis and urticarial vasculitis

Abstract: BACKGROUND It has been demonstrated that neutrophils, eosinophils and monocytes, under appropriated stimulus, may express tissue factor and therefore, activate the extrinsic pathway of coagulation. We performed a transversal and case-control study of patients with chronic urticaria and patients with psoriasis, in our outpatient clinic to evaluate the production of D-dimer. OBJECTIVE To evaluate D-dimer serum levels in patients with chronic urticaria and its possible correlation with disease activity. PATIENT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…In patients with CU, the increased level of D-dimer and its association with disease severity has been also confirmed in other studies (52)(53)(54). In addition, it has been shown that patients with active CU have elevated plasma D-dimer levels compared to patients with CU in remission and patients with psoriasis (53).…”
Section: Coagulation Biomarkers In Chronic Urticariasupporting
confidence: 66%
“…In patients with CU, the increased level of D-dimer and its association with disease severity has been also confirmed in other studies (52)(53)(54). In addition, it has been shown that patients with active CU have elevated plasma D-dimer levels compared to patients with CU in remission and patients with psoriasis (53).…”
Section: Coagulation Biomarkers In Chronic Urticariasupporting
confidence: 66%
“…By releasing potent vasoactive mediators, vasodilation is induced, increasing capillary permeability and resulting in erythema and papule formation. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, eosinophils might be in turn activated and recruited by mediators, cytokines, chemokines, or other as yet unknown factors released by mast cells [15][16][17][18]. The findings summarized above have been confirmed by several independent groups [19][20][21][22][23][24][25][26]. Thus, it seems likely that coagulation may play a role in the pathogenesis of chronic urticaria.…”
Section: Introductionmentioning
confidence: 95%